Analisis Faktor-faktor yang Mempengaruhi Penghimpunan Deposito Mudharabah Perbankan Syariah di Indonesia - Novianto, Abdullah Syakur; Hadiwidjojo, Djumilah (Jurnal Aplikasi Manajemen, 2013)
This study aims to analyze the factors that affect the collection of mudaraba deposits in Islamic banks in Indonesia, with observation period since 2005 to 2013. Vector auto regression (VAR) is used to analysis data in this study. The results showed that gross domestic product (GDP) and number of offices have significant effect on mudaraba deposits, while inflation rate and rate of profit sharing not affect mudaraba deposits.